Tanfîdz Dars Idhâfiy fî al-Lughah al-‘Arabiyyah min Mandzûr Nadzâriyah Sulûkiyyah - Zarkasyi, Ahmad Hidayatullah; Nurjanah, Anita; Wahyudi, Muhammad; Azmi, Dhea Fairuz (Postgraduate of IAIN Metro Lampung Indonesia, 2023)
Darussalam Gontor Modern Islamic Institution is an educational institution that inculcates learning Arabic, one of which is supplementary language subject. Supplementary language subject was held for new or beginner female students, namely grades 1, 1 Intensive, and 2. This research chooses grade 1 because most of them experienced difficulties and disliked the language. Therefore, the research is interested in further studying the application of supplementary language subject according to Behavioristic Theory and the application of behavioristic theory in supplementary language subject at Darussalam Gontor Modern Islamic Institution for Girls First Campus. The purpose of this research is to describe the application of supplementary language subject for student of class 1 according to Behavioristic Theory and the application of Behavioristic Theory in supplementary language subject at Darussalam Gontor Modern Islamic Institution for Girls First Campus. The research method used is a qualitative approach that is descriptive in the form of a case study research method, with data collection techniques through observation, interviews and documentation. The results of this study indicate that in supplementary language subject activities an appropriate stimulus response is needed. The stimulus provided by the tutor includes giving examples, advice, and warnings, as well as giving gifts. Class 1 female students responded positively, namely there was a change in mindset to always speak by formal language every day and there was a change in behavior, namely mentioning, answering, asking, conveying, responding, and commenting.